Role of endothelial cells in graft-versus-host disease - Neidemire-Colley, Lotus; Robert, Jérémy; Ackaoui, Antoine; Dorrance, Adrienne M.; Guimond, Martin; Ranganathan, Parvathi (Frontiers in Immunology, 2022)
Allogeneic hematopoietic transplantation (allo-HCT) is the only curative treatment for patients with refractory or high-risk hematologic malignancies who do not respond to conventional chemotherapy. Acute graft-versus-host disease (GVHD) mediated by alloreactive T cells in the donor graft is a frequently fatal complication and the leading cause of non-relapse mortality (NRM) in patients post allo-HCT. The pathogenesis of acute GVHD involves recognition of minor and/or major HLA mismatched host antigens by donor T cells followed by expansion, migration and finally end-organ damage due to combination of inflammatory cytokine secretion and direct cytotoxic effects. The endothelium is a thin layer of endothelial cells (EC) that line the innermost portion of the blood vessels and a key regulator in vascular homeostasis and inflammatory responses. Endothelial cell activation and dysfunction plays a role in multiple post-transplant complications including but not limited to veno-occlusive disease (VOD), transplant associated thrombotic microangiopathy (TA-TMA), and idiopathic pneumonia syndrome, reviewed elsewhere. In this mini review, we summarize the biology of endothelial cells, factors regulating EC activation and the role of ECs in inflammation and GVHD pathogenesis.